Desain Human Machine Interface (HMI) Pada Sistem Pencetak Genteng Otomatis - Prasetyo, Yuli; Triyono, Budi; Nur Prakoso, Dimas; Jasa Kusumo Haryo, Raden (Universitas Darul Ulum, 2024)
Roof Tile Printing Machines are important equipment in the industry for printing roof tiles and managing the roof tile production process. This tile printing machine includes a press machine and conveyor that can be adjusted so that the system can operate optimally during production. Operating a tile printing machine requires a program that can control various machine functions, such as conveyor motors and pneumatic cylinders. These programs are generally implemented using a Programmable Logic Controller (PLC). Therefore, an automatic tile printing system based on PLC and HMI with pressure and current parameters was created. This system can control and monitor the tile printing system while operating via the HMI screen. This method is used to collect data related to working methods, diagrams, cable connections, PLC programs, and data management in the HMI. One method used involves components such as limit switches, pressure sensors, current sensors, and pneumatics. The data generated from these processes is processed in the PLC and displayed on the HMI screen. The results obtained from this system are capable of monitoring the tile printing process in real time via the HMI screen.